Reviving Smiles: The Essential Guide To Root Canal Treatment" (Journal of Namibian Studies : History Politics Culture, 2023)
Root canal treatment (RCT) is a crucial dental procedure aimed at preserving a tooth compromised by pulp infection or inflammation. "Reviving Smiles: The Essential Guide to Root Canal Treatment" presents comprehensive insights into the principles, techniques, and outcomes of RCT. This essential guide synthesizes contemporary research findings and clinical practices to offer a holistic understanding of RCT. Key topics covered include diagnosis of pulpal and periapical diseases, factors influencing treatment outcomes, regenerative endodontics, infection control measures, and the use of rubber dam isolation. By providing evidence-based recommendations and practical tips, this guide equips dental professionals with the knowledge and skills necessary to perform successful RCT and contribute to the restoration of patients' oral health and well-being.